Driving Local Productivity: The Interplay of MSMEs, Government Spending, and Economic Growth - Maria Septijantini Alie (Shirkah: Journal of Economics and Business, 2025)
The strategic development of Micro, Small, and Medium Enterprises (MSMEs) and government spending are pivotal drivers of local productivity and regional economic growth. However, existing empirical investigations often lack an integrated framework linking these crucial factors. This study addresses that gap by analyzing the influence of MSME growth and government spending on local sector productivity and their subsequent implications for economic growth dynamics in Lampung Province, Indonesia. Adopting a quantitative survey design, this research collected primary data from 190 purposively selected respondents, comprising MSME actors and government officials across key economic sectors. Supporting secondary data was also utilized. The study employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test seven hypotheses. The findings unequivocally demonstrate that MSME growth and government spending significantly influence the dynamic of economic growth and local sector productivity. Moreover, local sector productivity also significantly influences economic growth. Last but not least, both MSME growth and government spending have significant indirect influences on economic growth through local sector productivity. This study advances the understanding of the causal mechanisms linking fiscal policy and MSME dynamics within regional development frameworks. It further emphasizes the critical importance of synergy between local governments and MSME stakeholders to ensure inclusive and sustainable economic growth. Future research is encouraged to explore sector-specific policy impacts through longitudinal and mixed-method approaches for more profound insights.